Kontribusi Daya Ledak Otot Tungkai dan Koordinasi Mata-Tangan terhadap Kemampuan Jump Servis Bola Voli Klub PLT Putra Kampar - Sonia Ardila; Alficandra Alficandra (Journal of Innovative and Creativity, 2025)
The purpose of this study was to determine the contribution of lower limb explosive power and eye-hand coordination to the jump serve ability of the PLT Putra Kampar Volleyball Club. This research employed a correlational design. The population consisted of all athletes from the PLT Putra Kampar Club, totaling 15 individuals. The sampling technique used was total sampling, with a sample size of 15 athletes. The research instruments included a vertical jump test to measure lower limb explosive power, a tennis ball throw-and-catch test to assess eye-hand coordination, and a jump serve test for volleyball ability. Based on the results, it can be concluded that (1) there is a contribution of lower limb explosive power to the jump serve ability of the PLT Putra Kampar Volleyball Club by 37.58%, with a correlation coefficient (r) of 0.613 greater than the critical value (r table) of 0.514, categorized as strong; (2) eye-hand coordination contributes 52.85% to the jump serve ability, with an r value of 0.727 > 0.514, also categorized as strong; and (3) the combined contribution of lower limb explosive power and eye-hand coordination to the jump serve ability is 53.14%, with an r value of 0.729 > 0.514, again categorized as strong.